1998
DOI: 10.1006/viro.1997.8976
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Pulmonary Syndrome Outbreak in Argentina: Molecular Evidence for Person-to-Person Transmission of Andes Virus

Abstract: An increase of Hantavirus Pulmonary Syndrome (HPS) cases around a southwestern Argentina town and in persons living 1400 km away but in contact with those cases was detected during the spring of 1996. In order to evaluate person-to-person transmission we compared the homology of PCR-amplified viral sequences of 26 Argentine and Chilean cases. Sixteen of them were epidemiologically linked cases and had the same sequence (Epilink/96) in the S segment 3' noncoding region and in the M segment partial G1 and G2 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
266
0
20

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(301 citation statements)
references
References 35 publications
(42 reference statements)
4
266
0
20
Order By: Relevance
“…Interpersonal transmission of hantavirus has been reported only in Argentina and Chile, but further investigation indicated that this possibility is very unlikely [4][5][6] . The contact with hantavirus in and of itself does not cause HPS, since infection is dependent on the quantity of viral particles, such that lower concentrations of particles could lead to subclinical infection.…”
Section: Introductionmentioning
confidence: 97%
“…Interpersonal transmission of hantavirus has been reported only in Argentina and Chile, but further investigation indicated that this possibility is very unlikely [4][5][6] . The contact with hantavirus in and of itself does not cause HPS, since infection is dependent on the quantity of viral particles, such that lower concentrations of particles could lead to subclinical infection.…”
Section: Introductionmentioning
confidence: 97%
“…This infection must be differentiated from other causes of similar symptoms. Person-to-person transmission has been described in Argentina [4][5][6] and could not be excluded in two Andes virus-related family clusters from Chile [7], thus early diagnosis is crucial to prevent outbreaks and to perform a strict clinical follow-up of contacts. It has been considered desirable for confirmed cases of Andes virus infection to be isolated in separate care units and for 'droplet precautions' to be used [7].…”
Section: Introductionmentioning
confidence: 99%
“…In phylogenetic analysis, all viruses associated with cases of HPS from Argentina [6,19], Chile [20], Paraguay [21] and Uruguay (P. J. Padula, unpublished observations) and sigmodontine-related virus from Bolivia [22,23], clustered together with Andes virus [24] and some North American viruses like Sin Nombre (SN) [2,25], Bayou (BAY) [26] or Black Creek Canal (BCC) [27].…”
Section: Introductionmentioning
confidence: 99%
“…In Skandinavien haben epidemiologische Untersuchungen einen Anstieg der Rötelmaus-Populationsgröße in einem mehrjährigen Zyklus gezeigt, der mit der Häufigkeit von NE-Fällen korreliert [11]. Bisher gibt es nur für das hochvirulente, in Südamerika vorkommende Andesvirus (ANDV) einen Hinweis auf eine mögliche Übertragung von Mensch zu Mensch [12].…”
Section: Seroprävalenzunclassified